2021
DOI: 10.1111/apa.16027
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient urine collection methods for paediatric urinary tract infections: Systematic review of diagnostic accuracy studies

Abstract: Urinary tract infections (UTI), comprising cystitis and pyelonephritis, occur in 6% and 0.6% of acutely ill children presenting to primary care, respectively. 1,2 UTI diagnosis is important, as adequate and timely treatment can alleviate short-term distress of the child, prevent renal scarring 3 and progression to a more serious systemic infection. 4 Diagnosis is challenging, as only a minority of children with UTI present with typical UTI symptoms. In a previous study, we found that changes in urine appearanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Our findings also demonstrate the need for improved urine collection methods, such as a device which could make the urine collection process less challenging for parents and less distressing for the children. Previous literature, detailing the strengths and shortcomings of various methods of urine collection, including all of those discussed in our study, also points towards the need for new methods 2 4 11…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Our findings also demonstrate the need for improved urine collection methods, such as a device which could make the urine collection process less challenging for parents and less distressing for the children. Previous literature, detailing the strengths and shortcomings of various methods of urine collection, including all of those discussed in our study, also points towards the need for new methods 2 4 11…”
Section: Discussionmentioning
confidence: 75%
“…In one study, fewer than one-third of children who presented to primary care with acute illness and met microbiological criteria for UTI had been clinically suspected of having a UTI 3. Thus, there is a need for urine testing to exclude UTI in children where the cause of acute illness is unclear 4…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On this basis, the different international clinical practice guidelines have recommended the collection of urine cultures by CCUC, UC or suprapubic aspiration to establish a diagnosis of UTI, and UB is not considered as a valid method. [18][19][20]25,26 Sample contamination rates have been described to be between 4.5% and 39% for CCUC 5,6,[10][11][12]23,27,28 and between 1.6% and 14.3% for UC. 5,[10][11][12]23,[28][29][30] Labrosse et al found no significant differences in the contamination of samples obtained by CCUC and UC in infants younger than six months of age.…”
mentioning
confidence: 99%